Cardiac Surgery and Follow-up Diagnosis of the Left Ventricular Pseudoaneurysm Patient - Benincasa, Giulio; Parascandolo, Alessia; Bonavita, Raffaella; Bellino, Ilaria; Altiero, Michele; Schiavone, Vincenzo; Laukkanen, Mikko O.; Alfano, Gennaro (Cardiology and Cardiovascular Medicine, 2020)
Left ventricular pseudoaneurysms (LVP) are false aneurysms caused by the rupture of left ventricular wall as a complication of myocardial infarction, cardiac surgery, congenital heart disease, and, more rarely endocarditis. It is a rare condition that initiates 3-14 days are myocardial infarction affecting 0.5% of the patients. The known risk factors to develop LVP are age, history of hypertension, deficiency of collateral circulation after myocardial infarction, and female gender. The current case report describes LVP in a 58-year old male patient with frontal acute myocardial infarction history. The patient was diagnosed using ECG, CINE-MRI, DE-IR analysis, and thorax-CT followed by urgent cardiac surgery. The diagnosis was an apical pseudoaneurysm caused by previous myocardial necrosis. The Immunohistochemistry suggested cardiac fibrosis. The patient was discharged asymptomatic for angina pectoris, dyspnea and palpitations, and prescribed warfarin against clotting, β blocker/vasodilator, furosemide diuretic, angiotensin receptor blocker, and proton pump inhibitor medication. After six months of follow up, the patient demonstrated the absence of preoperative symptoms.